Uma análise acerca dos parcelamentos tributários especiais no município de Mossoró no ano de 2016 e seus efeitos na arrecadação e no comportamento dos contribuintes - Lima, Vitória Alves Martins de (Universidade Federal Rural do Semi-Árido, 2018)
Because of the economic crisis and the inefficiency of the tax collection system, it has been common to implement the so-called special tax installment by federal entities, aiming to increase tax collection and regularization of taxpayers, despite being an exceptional measure. This regular frequency of realization, while promoting an increase in short-term financial resources, may be generating other long-term consequences than those expected by the tax authorities. In view of these notes, this paper aims to: (i) to present the concept and characteristics of the institute called tax installment, with special emphasis on the special tax installment; (ii) to analyze, in a descriptive way, Municipal Complementary Law nº 112/2015, responsible for implementing the Tax Recovery Program (Refis) in Mossoró; and (iii) to address the context and reasons for the concession of special tax installment in the year 2016 in Mossoró City, to critically examine its effects on tax collection and taxpayers behavior, and to propose further measures to increase the collection.
Artigo Acadêmico
Keywords: Parcelamento tributário especial; Comportamento; Arrecadação; Efeitos; Special tax installments.; Behavior; Tax collection; Effects; CIENCIAS SOCIAIS APLICADAS::DIREITO